Programa de educación turística ambiental dirigido a las unidades educativas para el desarrollo sostenible del cantón Bolívar. - Avellán Bailón, Leonardo Fabián (2018)
The present investigation was developed with the purpose of making a situational diagnosis and at the same time promoting sustainable environmental tourism development in the area, through the proposed proposal of designing an educational program directed to the educational units of Bolívar canton. To comply with the proposed methodology was established the same as consisting of 3 phases, the first consisting of diagnosing the processes and organizations involved, defining and characterizing the area of study investigated, also conducting the analysis of tourism management through technical visits , matrices of involved and SWOT, for the second phase focused on the methodological and pedagogical guidelines to direct the development of the program, where guidelines were defined to guide the proposed proposal, in its last phase it was proposed to develop the tourism education program where objectives, strategies and indicators to be followed were established in the respective educational units selected. For the fulfillment of this phase, the document review, field observation and evaluation matrix and program monitoring were carried out. As a result, the study area was delimited by evaluating the processes proposed in the thesis development, and the statistical data collected in the application of interviews and feasibility surveys of the program to be carried out. In conclusion, the management of the program for educational units, showed that the tourism and academic sector will be benefited since it will serve socio-economic, environmental and tourist development for the population.